2006
DOI: 10.1097/01.inf.0000237797.14283.cf
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Efficacy and Safety of Live Attenuated Cold-Adapted Influenza Vaccine, Trivalent, With Trivalent Inactivated Influenza Virus Vaccine in Children and Adolescents With Asthma

Abstract: CAIV-T was well tolerated in children and adolescents with asthma. There was no evidence of a significant increase in adverse pulmonary outcomes for CAIV-T compared with TIV. CAIV-T had a significantly greater relative efficacy of 35% compared with TIV in this high-risk population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
157
2
10

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(175 citation statements)
references
References 32 publications
6
157
2
10
Order By: Relevance
“…Overall the frequency of grade 2 and grade 3 signs and symptoms, including pulmonary disease and asthma or wheezing, were equally distributed between the two treatment Arms. Injection site reactions for TIV were observed in 23% of recipients, including one grade 3 event, which is similar to that previously reported (23)(24)(25)(26). Mild upper respiratory symptoms were more commonly reported after LAIV (52%) than after TIV (31%), which has also been previously reported (23)(24)(25)(26).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Overall the frequency of grade 2 and grade 3 signs and symptoms, including pulmonary disease and asthma or wheezing, were equally distributed between the two treatment Arms. Injection site reactions for TIV were observed in 23% of recipients, including one grade 3 event, which is similar to that previously reported (23)(24)(25)(26). Mild upper respiratory symptoms were more commonly reported after LAIV (52%) than after TIV (31%), which has also been previously reported (23)(24)(25)(26).…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, because of intranasal administration, LAIV has the potential to stimulate greater local anti-influenza immune responses than TIV (20)(21)(22). LAIV demonstrated greater reductions in influenza than TIV in HIV-uninfected children, against strains that were well-matched with strains in the vaccine, as well as against antigenically drifted strains not included in the vaccine administered (23)(24)(25)(26)(27)(28), and several studies have shown that the LAIV protective effect can extend beyond the year of administration (27,28).…”
Section: Introductionmentioning
confidence: 99%
“…LAIV provided levels of efficacy against influenza illness that, in the three comparative studies conducted, were significantly higher than those provided by TIV 1 , 3 , 7 . In contrast, comparative studies in adults ≥18 years of age have demonstrated variable results; studies have demonstrated comparable protection of the two vaccines, 12 , 13 , 14 , 15 , 16 greater protection with TIV, 17 , 18 , 19 and, in some cases, greater protection with LAIV 19 .…”
Section: Introductionmentioning
confidence: 90%
“…Multiple prospective, randomized, controlled studies have described the efficacy of live attenuated influenza vaccine (LAIV) in children and adolescents compared with placebo and with trivalent inactivated influenza vaccine (TIV) 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 . LAIV provided levels of efficacy against influenza illness that, in the three comparative studies conducted, were significantly higher than those provided by TIV 1 , 3 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…For the age group 6-17 years, the only available data are those from the study by Fleming et al [15], which included approximately 2200 children with a clinical diagnosis of asthma. In this study, LAIV was 32% (95% CI: 3%-52%) more effective against laboratory-confirmed influenza than TIV (.…”
Section: Children Aged 6-17 Yearsmentioning
confidence: 99%